2015
DOI: 10.1007/s11120-015-0090-4
|View full text |Cite
|
Sign up to set email alerts
|

NDH-1L interacts with ferredoxin via the subunit NdhS in Thermosynechococcus elongatus

Abstract: The large size complex of cyanobacterial NAD(P)H dehydrogenase (NDH-1) complex (NDH-1L) plays crucial role in a variety of bioenergetic reactions such as respiration and cyclic electron flow around photosystem I. Although the complex has been isolated and identified, its biochemical function still remains to be clarified. Here, we highly purified the NDH-1L complex from the cells of Thermosynechococcus elongatus by Ni(2+) affinity chromatography and size-exclusion chromatography. The purified NDH-1L complex ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…8). This possibility was supported by the interaction of NdhS with Fd (He et al, 2015). The results of this study further suggested that NdhV may be essential to stabilize the binding of NdhS with Fd based on the following reasons: (1) NdhV interacts with NdhS; (2) deletion of ndhV had no effect on the amount of NdhS, but the deletion reduced the NDH-CET activity; and (3) reduction of NDH-CET activity was more significant in DndhS than in DndhV as deduced from the results of this study and a previous study (Battchikova et al, 2011b).…”
Section: Discussionmentioning
confidence: 89%
“…8). This possibility was supported by the interaction of NdhS with Fd (He et al, 2015). The results of this study further suggested that NdhV may be essential to stabilize the binding of NdhS with Fd based on the following reasons: (1) NdhV interacts with NdhS; (2) deletion of ndhV had no effect on the amount of NdhS, but the deletion reduced the NDH-CET activity; and (3) reduction of NDH-CET activity was more significant in DndhS than in DndhV as deduced from the results of this study and a previous study (Battchikova et al, 2011b).…”
Section: Discussionmentioning
confidence: 89%
“…In addition, the accumulation of NdhV was almost lost in the thylakoid membranes in M55 and in ΔNdhM (Fig. 4C) in which the hydrophilic subcomplex of NDH-1 complexes are degraded (He et al )20, but it was not affected either in NdhD3/D4 defective mutant (Fig. 4B) in which only NDH-1L and NDH-1M exist, or in NdhD1/D2 defective mutant (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…The chloroplast NDH-1 complex was proposed to accept electrons from Fd, and NdhS was suggested to be the Fd-binding subunit based on the overall spatial homology of NdhS and the PsaE subunit of the PSI complex (Yamamoto et al, 2011;Yamamoto and Shikanai, 2013). Cyanobacterial NdhS is homologous to its counterpart in chloroplasts, and the interaction of NdhS with Fd has been demonstrated in the cyanobacterium Thermosynechococcus elongatus (He et al, 2015). Thus, Fd is likely to be an electron donor to cyanobacterial NDH-1 complexes, at least to NDH-1L.…”
Section: Role Of the Ndh-1l-psi Supercomplex In Ndh-cetmentioning
confidence: 99%
“…Structurally, respiratory NDH-1 and photosynthetic NDH-1 contain a conserved L-shaped skeleton (Friedrich et al, 1995;Friedrich and Scheide, 2000;Arteni et al, 2006;Kou ril et al, 2014), but numerous oxygenic photosynthesis-specific subunits were added to the photosynthetic NDH-1 (for review, see Battchikova et al, 2011b;Ifuku et al, 2011;Peng et al, 2011a). Among them, the NdhS subunit can bind reduced Fd, which provides a functional link to the PSI complex that permits NDH-1-dependent cyclic electron transport (NDH-CET; Battchikova et al, 2011a;Yamamoto et al, 2011;Yamamoto and Shikanai, 2013;He et al, 2015).…”
mentioning
confidence: 99%